An examination of the relationships between vocational identity, hardiness, meaningful work, burnout, and work engagement - Loebel, Greg A., author; Dik, Bryan, advisor; Chavez, Ernest, committee member; Davalos, Deana, committee member; Conroy, Samantha, committee member (Colorado State University. Libraries, 2020)
A cross-sectional study was conducted to expand the Job Demands-Resources (JD-R) model and personal resources within the model. The association between vocational identity as a personal resource and two criterion variables of burnout and work engagement were examined in a sample of 255 full-time U.S. working adults using Amazon's Mechanical Turk to collect survey data. JD-R is situated within occupational stress research that incorporates burnout and work engagement as the two primary constructs other variables are related to. Vocational identity has seen very little research in working adult samples and has been limited to career development outcomes. Minimal examination has been conducted of core features of identity within the JD-R model. Therefore, this study explored vocational identity as a personal resource that predicts burnout and work engagement, hypothesizing a negative relationship with the former and positive relationship with the latter. Results indicated vocational identity had significant main effects on both work engagement and burnout. Additionally, the perception that one's work is meaningful was examined as an important job resource hypothesized to explain the relationship between the main predictor and criterion variables as a mediator. Results also indicated that meaningful work significantly mediated the direct effects of vocational identity on work engagement and burnout. Since stress is a natural part of work, one's stress appraisal and coping style has a significant influence on well-being outcomes. Hardiness, which is a personality style that influences how one may effectively cope with stress, is viewed as an important personal resource. It was hypothesized that hardiness moderated the strength of the direct relationship between vocational identity and the criterion variables, as well as the strength of the relationship with the meaningful work mediator. A proposed moderated mediation model was tested where vocational identity predicted burnout and work engagement through the mediating relationship of meaningful work. The mediated effect was expected to be stronger for those higher in hardiness. Results revealed that hardiness only had a moderating effect on the relationship between vocational identity and the exhaustion subscale of burnout, but no significant moderating effect was detected for the other two burnout subscales or any of the three work engagement subscales. Results also showed no detectable moderating effect of hardiness on the indirect relationship of vocational identity on work engagement and burnout through meaningful work.